In the mirror of transitology: The politics of power alternation in the Caucasus and Central Asia - S. A. Pritchin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In 2021 the countries of Central Asia and the South Caucasus celebrate the 30th anniversary of independence. According to the paradigm of transitology, the political development of a state since the departure from the authoritarian regime entails progressive liberalization and democratization of political processes. And, in accordance with the predominant theoretical approaches, the post-Soviet states were expected to follow this path. However, a closer look at the speciﬁ c scenarios of power alternation in the Central Asia and the South Caucasus provides a much more mixed picture: here the change of ruling elites took very diﬀ erent forms and shapes. The choice of scenario for the transfer of power was always determined by a complex combination of internal and external factors, including the nature and characteristics of the political system of a particular state, its ethnic com-position, the socio-economic situation and external environment. Nevertheless, it is possible to discern several key scenarios: a ‘revolutionary’ scenario, which implies a violent change of power; an intra-elite consensus; transition of power to a successor; a hereditary transmission of power; democratic elections; a resigna-tion of a president. A comparative analysis of the political processes unfolding in the region over the past 30 years shows that even institutionally the countries of Central Asia and the South Caucasus are not ready yet for a competition policy. Moreover, the latter is generally viewed by their leaders as a threat to both the stability of the state and to the interests of the ruling elites. To this may be added the expansion of diﬀ erent informal, archaic political practices across the post-Soviet space. The latter include the sacralization of power, when national interests are equated with the interests of the ruling clan and the whole national identity is built up around this nexus. All this shows the limits of classical transitology theory when it comes to political transformations in the post-Soviet space, which it is unable to explain, yet alone to predict their possible future development. Thus, there is a strong need to develop new theoretical frameworks that would better accommodate particularities of the regional political systems.